(untitled) (KYAMC Journal, 2013)
Identification of impurities and their amounts in the atorvastatin bulk drug and tablet DIVASTINTM (20 mg) were done using HPLC with diode array detector. The composition of mobile phase was acetonitril:phosphate buffer (45:55%; pH 4.0) with flow rate of 0.5 mL/min and detected at 248 ± 8 nm. Four impurities (desfluoro atorvastatin, distereoisomer, 3-o-methyl atorvastatin and lactone atorvastatin) were detected in the bulk drug whereas five impurities were detected in the tablet DIVASTINTM (20 mg). The total amounts of impurities in atorvastatin bulk drug and tablet were 0.804 and 0.983% respectively. In conclusion, the total amount of impurities was less than 1% which is acceptable. DOI: http://dx.doi.org/10.3329/kyamcj.v1i2.13313 KYAMC Journal Vol.1(2) January 2011, 43-47